2017
DOI: 10.1021/acsenergylett.7b00525
|View full text |Cite
|
Sign up to set email alerts
|

Current-Induced Phase Segregation in Mixed Halide Hybrid Perovskites and its Impact on Two-Terminal Tandem Solar Cell Design

Abstract: Mixed halide hybrid perovskites are of significant interest because their bandgap can be tuned as a current-matched top-cell in tandem photovoltaics. However, several mixed halide perovskites phase segregate under illumination, exhibit large voltage deficits, and produce unstable photocurrents. We investigate the origin of phase segregation and implication for tandems with mixed halide large-bandgap (∼1.75 eV) perovskites. We show explicitly that MAPb­(I0.6Br0.4)3 and (MA0.9,Cs0.1)­Pb­(I0.6,Br0.4)3, termed “MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
253
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(277 citation statements)
references
References 41 publications
13
253
1
Order By: Relevance
“…The steady‐state current‐stability of other devices is summarized in Figure S5 (Supporting Information). Consistent with the phase‐stability (Figure S4, Supporting Information) and device hysteresis results (Figure 6a),50,52 all the devices exhibit reduction of photo‐current at the beginning of illumination, and the MAPb(I 0.6 Br 0.4 ) 3 device has the fastest degradation.…”
Section: Device Performance Of Pvscs Prepared With Different Perovskisupporting
confidence: 78%
“…The steady‐state current‐stability of other devices is summarized in Figure S5 (Supporting Information). Consistent with the phase‐stability (Figure S4, Supporting Information) and device hysteresis results (Figure 6a),50,52 all the devices exhibit reduction of photo‐current at the beginning of illumination, and the MAPb(I 0.6 Br 0.4 ) 3 device has the fastest degradation.…”
Section: Device Performance Of Pvscs Prepared With Different Perovskisupporting
confidence: 78%
“…Notably, our device exhibits low efficiency roll‐off, indicating a balanced charge injection and recombination . It is worth emphasizing that the stability of the EL spectra is mainly attributed to the balanced charge injection resulting from the co‐HTLs structure, as K + ‐based single HTL device undergoes phase segregation under constant voltage (Figure S13, Supporting Information). Furthermore, through optimizing the device structure, the optimized blue perovskite NC‐LED achieves a state‐of‐the‐art EQE among the blue PeLEDs based on NCs .…”
Section: Resultsmentioning
confidence: 85%
“…The first method is the use of mixed‐halide perovskites . Because of the halide segregation, an irreversible emission shift can occur during the bias operation in these mixed‐halide‐based blue PeLEDs. The second method is the use of perovskite nanoplatelets by inserting large organic cations to form a quasi‐two‐dimensional (quasi‐2D) phase .…”
Section: Introductionmentioning
confidence: 99%
“…However, photoluminescence (PL) and X‐ray diffraction (XRD) techniques have shown that upon illumination the halide ions within some mixed‐halide perovskites demix to form regions of differing composition—and differing bandgap—within the same perovskite film . The spontaneous halide segregation and formation of a spatially inhomogeneous bandgap diminishes the charge‐carrier transport properties of the perovskite film and undermines the value of a selectable bandgap, dramatically reducing the viability of these materials for use as part of a tandem solar device . Interestingly, once the perovskite film is removed from the illumination source, the segregated halide ions remix over the course of tens of minutes to hours, and the film returns to its initial state .…”
Section: Introductionmentioning
confidence: 99%